Simultaneous identification of GSTP1 Ile105→Val105 and Ala114→Val114 substitutions using an amplification refractory mutation systempolymerase chain reactionassay: studies in patients with asthma - Hemmingsen, Anja (BioMed Central, 2001)
BACKGROUND: The glutathione S-transferase (GST) enzyme GSTP1 utilizes byproducts of oxidative stress. We previously showed that alleles of GSTP1 that encode the Ile105→Val105 substitution are associated with the asthma phenotypes of atopy and bronchial hyperresponsiveness (BHR). However, a further polymorphic site (Ala114→Val114) has been identified that results in the following alleles: GSTP1(*)A (wild-type Ile105→Ala114), GSTP1(*)B (Val105→Ala114), GSTP1(*)C (Val105→Val114) and GSTP1(*)D (Ile105→Val114). METHODS: Because full identification of GSTP1 alleles may identify stronger links with asthma phenotypes, we describe an amplification refractory mutation system (ARMS) assay that allows identification of all genotypes. We explored whether the GSTP1 substitutions influence susceptibility to asthma, atopy and BHR. RESULTS: Among 191 atopic nonasthmatic, atopic asthmatic and nonatopic nonasthmatic individuals, none had the BD, CD, or DD genotypes. GSTP1 BC was significantly associated with reduced risk for atopy (P = 0.031). Compared with AA, trend test analysis identified a significant decrease in the frequency of GSTP1 BC with increasing severity of BHR (P = 0.031). Similarly, the frequency of GSTP1 AA increased with increasing BHR. CONCLUSION: These data suggest that GSTP1(*)B and possibly GSTP1(*)C are protective against asthma and related phenotypes.